2018
DOI: 10.1186/s12882-017-0802-4
|View full text |Cite
|
Sign up to set email alerts
|

Treating C3 glomerulopathy with eculizumab

Abstract: BackgroundC3 glomerulopathy (C3G) is a rare, but severe glomerular disease with grim prognosis. The complex pathogenesis is just unfolding, and involves acquired as well as inherited dysregulation of the alternative pathway of the complement cascade. Currently, there is no established therapy. Treatment with the C5 complement inhibitor eculizumab may be a therapeutic option. However, due to rarity of the disease, parameters predicting treatment response remain largely unknown.MethodsSeven patients with C3G (fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…The reasons are still unclear, and further studies are required. It’s presumed that uncontrolled activation of the complement pathway leads to predominantly glomerular deposition of C3, which is called C3 glomerulopathy . Based on that, we believe reduced C3 levels, as a result of overconsuming, may be highly associated with renal involvement.…”
Section: Discussionmentioning
confidence: 96%
“…The reasons are still unclear, and further studies are required. It’s presumed that uncontrolled activation of the complement pathway leads to predominantly glomerular deposition of C3, which is called C3 glomerulopathy . Based on that, we believe reduced C3 levels, as a result of overconsuming, may be highly associated with renal involvement.…”
Section: Discussionmentioning
confidence: 96%
“…reported that creatinine level in one transplant recipient remained stable and in two transplant recipients was improved. Proteinuria remained stable in one patient and decreased in two patients [26].…”
Section: Discussionmentioning
confidence: 83%
“…Eculizumab is a humanized monoclonal antibody that binds C5 and prevents assembly of the membrane attack complex (C5b-9) thereby blocking the final complement cascade and reducing uncontrolled activation of the alternative complement pathway ( 35 ). Several case reports and open-label studies have already shown a potential benefit of eculizumab for patients with C3 glomerulonephritis and aHUS where there is an acquired dysregulation of complement factors ( 35 38 ). In addition, avacopan, a C5a receptor inhibitor, downregulates activation of the alternative complement pathway and has been shown to be an effective add-on therapy for ANCA associated vasculitis ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%